27-GAUGE PARS PLANA/PLICATA VITRECTOMY FOR PEDIATRIC VITREORETINAL SURGERY. Issue 2 (February 2023) - Ung, Cindy; Yonekawa, Yoshihiro; Chung, Mina M.; Berrocal, Audina M.; Kusaka, Shunji; Oshima, Yusuke; Chan, R. V. Paul; Inoue, Makoto; Read, Sarah P.; Kuriyan, Ajay E.; Todorich, Bozho; Thanos, Aristomenis; et al.
Abstract : The authors report a multicenter pilot study examining the use of 27-G vitrectomy and instrumentation in pediatric patients, ranging from premature infants with retinopathy of prematurity, to older children with traumatic macular hole and endophthalmitis. Abstract : Purpose: To report on the feasibility of 27-gauge (G) vitrectomy for pediatric patients. Methods: This study is an international, multicenter, retrospective, interventional case series. Participants were patients 17 years or younger who underwent 27-G vitrectomy for various indications. Results: The records of 56 eyes from 47 patients were reviewed. Mean age was 5.7 ± 5.2 years. Diagnoses included retinopathy of prematurity (Stages 3 with vitreous hemorrhage, 4A, 4B, and 5), Terson's syndrome, traumatic macular hole, posterior capsular opacification, endophthalmitis, and others. Instruments used were the 27-G infusion, 27-G vitreous cutter, 27-G light pipe, and 27-G internal limiting membrane forceps. Instrument bending was noted in one (1.8%) case. There were no cases with intraoperative complications, infusion issues, or postoperative endophthalmitis. There were 67/145 (46%) sclerotomies that required suturing, of which most (51/145) were sutured out of precaution. There were four cases (7.1%) that required conversion to a larger gauge and three cases (5.3%) that developed postoperative hypotony. Mean visual acuity improved from logarithm of the minimum angle of resolution 1.32 (20/420) to 0.72 (20/105), after a mean follow-up of 125.1 days ( P = 0.01). Anatomic success was achieved in 96.4% of eyes after a single surgery. Conclusion: Twenty-seven-gauge vitrectomy was safe and feasible in selected pediatric vitreoretinopathies. Further studies are warranted to examine indications and outcomes.